2000
DOI: 10.1677/joe.0.1660063
|View full text |Cite
|
Sign up to set email alerts
|

Three novel paralogs of the rodent prolactin gene family

Abstract: The prolactin (PRL) family consists of a collection of genes expressed in the uterus, placenta and anterior pituitary. These cytokines/hormones participate in the control of maternal-fetal adaptations to pregnancy. In this report, we establish the presence of three new members of the PRL family. Novel expressed sequence tags (ESTs) with homology to PRL were isolated from embryonic and placental cDNA libraries. The cDNAs were sequenced and compared with those of other members of the PRL family. The three new cD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 59 publications
1
21
0
Order By: Relevance
“…Cryosections (10 m) of tissues were prepared and stored at -80°C until used. Plasmids containing cDNAs for mouse Dprp and Plp-j (Orwig et al, 1997b;Dai et al, 2000) were used as templates to synthesize sense and antisense digoxigeninlabeled riboprobes according to the manufacturer's instructions (Roche Molecular Biochemicals, Indianapolis, IN).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Cryosections (10 m) of tissues were prepared and stored at -80°C until used. Plasmids containing cDNAs for mouse Dprp and Plp-j (Orwig et al, 1997b;Dai et al, 2000) were used as templates to synthesize sense and antisense digoxigeninlabeled riboprobes according to the manufacturer's instructions (Roche Molecular Biochemicals, Indianapolis, IN).…”
Section: In Situ Hybridizationmentioning
confidence: 99%
“…PRL is a member of a larger collection of structurally-related hormones/cytokines (the PRL superfamily) with an array of different biological targets and actions (Wiemers et al, 2003;Soares, 2004;Alam et al, 2006). In the rat and mouse, four members of the PRL superfamily are expressed in uterine decidua: decidual prolactin-related protein (DPRP; DTPRPMouse Genome Informatics) (Roby et al, 1993;Lin et al, 1997;Orwig et al, 1997b), prolactin-like protein B (PLP-B; PRLPBMouse Genome Informatics) (Duckworth et al, 1988;Croze et al, 1990;Cohick et al, 1997;Müller et al, 1998), PLP-J (PRLPJMouse Genome Informatics) (Hiraoka et al, 1999;Ishibashi and Imai, 1999;Toft and Linzer, 1999;Dai et al, 2000) and prolactin itself (Prigent-Tessier et al, 1999;Kimura et al, 2001). Each of these decidual PRL family cytokines can be viewed as a downstream mediator of intrauterine progesterone action.…”
Section: Introductionmentioning
confidence: 99%
“…The trilaminar trophoblast includes a single layer of mononuclear sinusoidal trophoblast giant cells (S-TGCs) that line the maternal blood sinusoids (Coan et al, 2005;Simmons and Cross, 2005;Simmons et al, 2007), and two layers of syncytiotrophoblast, SynT-I and -II, the latter of which is in contact with fetal endothelial cells (Simmons and Cross, 2005;Watson and Cross, 2005). The STGCs are secretory in nature, expressing hormones such as placental lactogen II (Campbell et al, 1989;Dai et al, 2000;Deb et al, 1991;Ishida et al, 2004;Lee et al, 2003;Sahgal et al, 2000;Simmons and Cross, 2005;Simmons et al, 2007), and are therefore likely to have a primary endocrine function. S-TGCs are loosely attached to the underlying syncytial layers via desmosomal adhesions and contain fenestrations to allow the SynT-I cells direct access to maternal blood (Coan et al, 2005;Davies and Glasser, 1968;Hernandez-Verdun, 1974).…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that PLP-J mRNA production is limited to early gestation, (peaking on day 7, and beginning to decrease on day 9, with undetectable levels by day 11) using the technique of in situ hybridization in placental tissue with a PLP-J probe. Another study demonstrated that the decidual expression of PLP-J is independent of extra-embryonic or embryonic factors (12).…”
Section: Introductionmentioning
confidence: 99%